The Relationship between Government Debt and Economic Growth in South Africa with Specific Reference to Eskom: Array - Zondi, Philani; Robinson, Zurika (EuroEconomica, 2021)
The increasing level of government debt continues to be one of the most contestable topics since the great recession due to its effect on growth; however, a consensus is yet to be achieved on the topic. The current study investigated the economic effects of deteriorating South African government debt for the period 1994 to 2019 with the application of the autoregressive distributed lag model by Pesaran et al. (1999), which generates efficient results in the presence of cointegration, yielding unbiased long-run estimates. In contrast to similar empirical studies, the analysis of Eskom’s output on growth was found to be crucial. The bounds test exhibited that the regressors were cointegrated in the long run. The results infer that in the short run, government debt has a positive but weak influence on the economic growth rate. Although negative in the long run, debt does not Granger-cause growth. The results also showed that Eskom’s output was negatively associated with economic growth in the long run and that government debt Granger-caused Eskom’s output level.